2021
DOI: 10.1088/1361-6528/ac0a16
|View full text |Cite
|
Sign up to set email alerts
|

Multielement 2D layered material photodetectors

Abstract: The pronounced quantum confinement effects, outstanding mechanical strength, strong lightmatter interactions and reasonably high electric transport properties under atomically thin limit have conjointly established 2D layered materials (2DLMs) as compelling building blocks towards the next generation optoelectronic devices. By virtue of the diverse compositions and crystal structures which bring about abundant physical properties, multielement 2DLMs (ME2DLMs) have become a bran-new research focus of tremendous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 232 publications
0
13
0
Order By: Relevance
“…[ 16 ] The diverse characteristics of ternary materials, which are endowed by the multiple degrees of freedom in composition, are more conducive to constructing multifunctional optoelectronic devices. [ 17 ] For example, Zhao et al. have demonstrated visible to mid‐infrared broadband photodetection (532 nm to 3.1 µm) based on narrow‐bandgap 2D Nb 2 SiTe 4.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 16 ] The diverse characteristics of ternary materials, which are endowed by the multiple degrees of freedom in composition, are more conducive to constructing multifunctional optoelectronic devices. [ 17 ] For example, Zhao et al. have demonstrated visible to mid‐infrared broadband photodetection (532 nm to 3.1 µm) based on narrow‐bandgap 2D Nb 2 SiTe 4.…”
Section: Introductionmentioning
confidence: 99%
“…[16] The diverse characteristics of ternary materials, which are endowed by the multiple degrees of freedom in composition, are more conducive to constructing multifunctional optoelectronic devices. [17] For example, Zhao et al have demonstrated visible to mid-infrared broadband photodetection (532 nm to 3.1 µm) based on narrow-bandgap 2D Nb 2 SiTe 4. [18] In another study, Zhou et al have realized a polarization-sensitive photodetector by employing a low-symmetry 2D PbSnS 2 nanosheet as the photosensitive channel.…”
Section: Introductionmentioning
confidence: 99%
“…Several important applications including sensors 3 , memory devices 4 , photovoltaics 5 , atomically-thin holograms 6 , electrically and optically modulated high harmonic generation 7 9 based on vdW layered materials have been demonstrated to substantiate their prospects till date. Noticeably, these applications are primarily realized on traditional mono- and binary-element vdW layered materials such as graphene, black phosphorous, GeAs, ReS 2 and transition metal dichalcogenides, therefore the material-associated inherent limitations such as elementary crystal structures, simple chemical compositions, material-dependent electronic and optical responses make the applications relatively monotonous and further confine their adaptability 10 13 . To address these limitations of mono- and binary-element materials, multi-element vdW layered materials 14 , 15 facilitate an alternative and versatile testbed for realizing innovative electronic, photonic and optoelectronic applications 10 12 , according to their complex crystal structures, stoichiometric variations, and exceptional physical and chemical properties such as high charge carrier mobility 10 , 16 , favorable band structure 17 , unique phonon vibrations 11 , 17 , linear dichroism transition 18 , 19 , and robust air stability.…”
Section: Introductionmentioning
confidence: 99%
“…Nowadays, van der Waals (vdW) nanomaterials has been established as a promising platform to understand light-matter interactions at subwavelength scale and create building blocks for optoelectronic and nanophotonic applications, due to their strong quantum confinement effects, dangling-bond-free surface, interlayer coupling, and anisotropic physical responses 1 6 . Since the successful mechanical isolation of naturally occurring two-dimensional (2D) materials 7 , unprecedented efforts have been shown in thriving its prospect in the technological improvisation ranging from energy storage to optoelectronic applications 2 , 5 , 8 , 9 .…”
Section: Introductionmentioning
confidence: 99%